Carbon-based gas-water composite gel for efficient interface evaporation as well as preparation method and application of carbon-based gas-water composite gel
By preparing carbon-based gas-water composite gel, using capillary action and environmental energy, the problems of stability and evaporation rate of hydrogel interface evaporator in high salinity seawater are solved, and rapid water supply and efficient evaporation are achieved, and the The long-term stability and efficient performance of the evaporator.
Patent Information
- Application Number
- CN202411299196.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
AI Technical Summary
The existing hydrogel interface evaporators are difficult to maintain stability and efficient evaporation rate in high salinity seawater, and the water transport capacity is insufficient, resulting in a shrinkage of the evaporator shape and a decrease in evaporation efficiency.
The PAN nanofiber membrane was prepared by electrospinning method using carbon-based gas-water composite gel, and sodium alginate was mixed, freeze-dried and calcined, and tanninic acid/PVA solution was added dropwise to form a carbon-based gas-water composite gel , utilize capillary action and ambient energy to enhance the evaporation rate.
It realizes rapid water supply in a high salinity environment, maintains the stability of the evaporator, reduces the equivalent evaporation enthalpy of water, improves the interface evaporation rate, and has good salt resistance and long-term salt resistance.
Smart Images

Figure CN119113945A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solar seawater desalination and relates to a carbon-based gas-water composite gel for efficient interface evaporation and a preparation method and application thereof. Background Art
[0002] Solar-driven interfacial evaporation to obtain fresh water has attracted widespread attention due to its high efficiency, low consumption, and environmental friendliness. Currently, many studies focus on optimizing thermal positioning to maximize the use of thermal energy, regulating water supply to ensure the sustainability of interfacial evaporation, and reducing the equivalent evaporation enthalpy of water to increase the interfacial evaporation rate.
[0003] Hydrogel is one of the most common evaporators. A water molecule usually forms a tetrahedral structure with four surrounding water molecules through hydrogen bonding, which is called free water. The hydrophilic chain network of the hydrogel interacts with adjacent water molecules through strong hydrogen bonds to form bound water. The intermediate water exists between bound water and free water, forming fewer or weaker hydrogen bonds with the surrounding water molecules and macromolecular chains, making it easier to escape from the hydrogen bond network. Literature 1 (Changxia Li, Sijia Cao, Jana Lutzki, et al, A Covalent Organic Framework / Graphene Dual-Region Hydrogel for Enhanced Solar-Driven Water Generation, Journal of the American Chemical Society, 2022 144(7), 3083-3090) developed a covalent organic framework / graphene dual-region hydrogel that contains hydrophilic and hydrophobic regions in one material. By precisely controlling the two wetting regions, the equivalent evaporation enthalpy of water can be optimized. When used as an interfacial evaporator, the evaporation rate is as high as 3.69 kg m -2 h -1. On the other hand, absorbing energy from the environment is also an effective way to increase the evaporation rate. This method requires that the interfacial evaporator has sufficient side area. Reference 2 (Yuefei Li, Jiyuan Zhu, Jiurui Liu, et al, Pyramid-shaped solar evaporator with high-efficient interfacial evaporation and salt harvesting capability, Journal of Cleaner Production, 2024, 434, 139956) manufactured a series of pyramid-shaped solar evaporators. With their excellent light capture and photothermal conversion capabilities, controlled water supply, effective thermal management, and energy input from the environment, the highest evaporation efficiency can reach 3.54 kg m -2 h -1 .
[0004] However, the preparation of hydrogel interfacial evaporators with the function of absorbing heat from the environment faces challenges. In order to obtain more heat from the environment, the evaporator usually needs to be a certain height above the water surface. Therefore, the evaporator needs excellent water transport capacity. Although hydrogels can reduce the evaporation enthalpy of water, water transport in hydrogels is mainly driven slowly by osmotic pressure, and the movement of water molecules is hindered by polymer chains. In addition, it is difficult to generate effective convection in the dense pore structure inside the hydrogel, which hinders the rapid downward transmission of salt ions. Due to the salting-out effect, the high concentration of ions at the top leads to the aggregation of polymer molecular chains. Therefore, the top of the three-dimensional hydrogel evaporator is usually dehydrated, especially when the evaporator is exposed to seawater at a certain height above the water surface and with high salinity, the shape of the evaporator will shrink, which is not conducive to long-term stable evaporation. Summary of the invention
[0005] Technical problem to be solved: In view of the deficiencies in the prior art, the present invention provides a carbon-based gas-water composite gel for efficient interfacial evaporation and a preparation method and application thereof.
[0006] Technical solution: A method for preparing a carbon-based gas-water composite gel for efficient interfacial evaporation, comprising the following steps: Step 1, using a polyacrylonitrile (PAN) solution in N, N-dimethylformamide (DMF) as a spinning solution, wherein the concentration of PAN is 10-15wt.%, and obtaining a PAN nanofiber membrane by electrospinning; Step 2, mixing the PAN nanofiber membrane with an aqueous sodium alginate solution, wherein the mass ratio of PAN to sodium alginate (SA) is 1:(0.8-1.2), and stirring to obtain a uniformly dispersed PAN / SA solution. liquid; step 3, pouring the PAN / SA uniform dispersion into a mold, and freeze-drying to obtain a composite aerogel; step 4, calcining the composite aerogel for 1 to 3 hours to obtain a composite carbon aerogel; step 5, dropping a tannic acid / PVA solution on the surface of the composite carbon aerogel, wherein the concentration of tannic acid in the solution is 0.1-0.5wt.%, the concentration of PVA is 2.5-7.5wt.%, and the mass of the dropped solution is 15-25 times the mass of the aerogel, followed by 1-5 freeze-thaw cycles to obtain a carbon-based air-water composite gel.
[0007] Preferably, in step 1, the weight average molecular weight of PAN is 149,000 to 151,000, and the concentration of PAN in the DMF solution of PAN is 13 wt.%.
[0008] Preferably, in step 1, the voltage of electrospinning is 18-21 kV, the liquid feeding speed is 1.5-3 mL / h, the distance between the needle and the receiver is 12 cm, and the spinning time is 12 h.
[0009] Preferably, in step 2, the concentration of the sodium alginate (SA) solution is 0.5 wt.% to 1 wt.%, and the mass ratio of PAN to SA is 1:1.
[0010] Preferably, in step 2, the stirring speed is 30000-32000 rpm, and the stirring time is 10-15 min.
[0011] Preferably, in step 4, the heating rate of the calcination is 5°C / min, and the nitrogen flow rate is 0.1 to 0.2 L / min.
[0012] Preferably, in step 5, the concentration of tannic acid is 0.1wt.%, the concentration of PVA is 5wt.%, the solvent is a mixture of ethanol and water, and the volume ratio of ethanol to water is 1:9.
[0013] Preferably, in step 5, the freezing temperature is -20°C, the freezing time is 7.5 to 8.5 hours, the thawing temperature is 10 to 25°C, and the thawing time is 8 to 10 hours.
[0014] The carbon-based air-water composite gel prepared by the above preparation method.
[0015] The above carbon-based air-water composite gel is used in solar interfacial evaporation seawater desalination.
[0016] The present invention prepares super-hydrophilic carbon aerogel by freeze drying and high-temperature calcination. Then, a tannic acid / polyvinyl alcohol solution is dripped onto the surface of the aerogel. Driven by capillary force, the solution spontaneously and evenly diffuses throughout the aerogel, forming a thin film on the aerogel skeleton. Then, a carbon-based air-water composite gel is obtained by cyclic freezing and thawing. When interfacial evaporation is performed, seawater can spontaneously reach the top rapidly through capillary force, thereby ensuring the sustainability of interfacial evaporation. At the same time, the tannic acid / PVA hydrogel can reduce the equivalent evaporation enthalpy of water and enhance the interfacial evaporation rate by synergistically absorbing the energy of the side wall environment.
[0017] Beneficial effects: (1) The carbon-based air-water composite gel prepared by the present invention retains the porous structure inside the aerogel, which can achieve rapid water supply, so that it can work in a high-salinity environment without dehydration.
[0018] (2) The carbon-based gas-water composite gel prepared by the present invention can not only reduce the evaporation enthalpy of water during interface evaporation, but also absorb heat from the environment, thus having a faster evaporation rate.
[0019] (3) The seawater desalination evaporation device of the present invention has a good salt blocking effect and maintains high evaporation efficiency and excellent salt resistance in long-term seawater desalination. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Flow chart of the preparation of carbon-based air-water composite gel.
[0021] Figure 2 This is a scanning electron microscope image of the carbon-based air-water composite gel prepared in Example 2.
[0022] Figure 3 This is a scanning electron microscope image of the carbon-based air-water composite gel prepared in Comparative Example 2.
[0023] Figure 4 It is the evaporation rate graph of Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0024] Figure 5 It is a long-term evaporation rate diagram of Example 2, Example 3, Example 4 and Comparative Example 1 and Comparative Example 2.
[0025] Figure 6 This is a comparison diagram of Example 2 before and after evaporation in 20 wt.% concentration brine.
[0026] Figure 7 This is a comparison chart of Comparative Example 2 before and after evaporation in 20wt.% concentration brine.
[0027] Figure 8 Example 2: Na in fresh water collected after seawater desalination + , K + Mg 2+ , Ca 2+ Comparison of the concentration of ions in the original seawater.
[0028] Fig. 9 This is the evaporation rate of Example 2 when evaporating NaCl solutions of different concentrations. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0030] Example 1
[0031] (1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0032] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0033] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0034] (2) Seawater desalination performance test:
[0035] Using a sunlight-simulated xenon lamp as the light source, simulating seawater as a 3g / 100mL sea salt solution, and using composite carbon aerogel, a seawater desalination evaporation device was constructed: Pearl cotton foam was used as the supporting material, and the composite carbon aerogel was stuck in the hole in the center of the foam. The height of the composite carbon aerogel exposed to the water surface was adjusted to 4cm, and a beaker was used as a seawater container. The light intensity of the sunlight-simulated xenon lamp was adjusted to 1kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. The calculation formula for the evaporation rate v is shown below, and the test results are shown in Figure 4 .from Figure 4 It can be seen that the evaporation rate is 3.87 kg m-2 h -1 .
[0036]
[0037] Where m is the mass of evaporated water, S is the illuminated area, and t is the evaporation time.
[0038] Example 2
[0039] (1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0040] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0041] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0042] 0.1g tannic acid, 5g PVA, 10g ethanol, and 85g water were added to a beaker and heated and stirred until dissolved. Then, the mixture was added dropwise to the surface of CNFA (tannic acid / PVA solution: CNFA = 20g: 1g). After a few minutes, the solution was evenly diffused, frozen at -20°C for 8h, and then thawed for 8h, and the cycle was repeated 3 times to obtain a carbon-based air-water composite gel.
[0043] Preparation process Figure 1 The scanning electron microscopy image of the prepared carbon-based air-water composite gel is shown in Figure 2 As shown in Figure 2, PAN nanofibers are coated on the SA nanosheet structure and still retain the porous structure.
[0044] (2) Seawater desalination performance test:
[0045] A solar-simulated xenon lamp was used as the light source, and a 3g / 100mL sea salt solution was used to simulate seawater. A seawater desalination evaporation device was constructed using carbon-based air-water composite gel: EPE foam was used as the supporting material, and the carbon-based air-water composite gel was stuck in the hole in the center of the foam. The height of the carbon-based air-water composite gel exposed to the water surface was adjusted to 4 cm, and a beaker was used as a seawater container. The light intensity of the solar-simulated xenon lamp was adjusted to 1 kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. Figure 4 Its evaporation rate is 4.21 kg m -2 h -1 . Continuous evaporation for 10 hours results are shown in Figure 5 , the evaporation rate can remain stable. The photos of Example 2 before and after evaporation in 20wt.% concentrated brine for 10h are shown in Figure 6 , basically no change.
[0046] Detection of Na in desalinated water + , K + Mg 2+ , Ca 2+ The ion concentration of Figure 8 The concentrations of all ions decreased by at least 2 orders of magnitude, indicating that the carbon-based air-water composite gel can effectively purify seawater.
[0047] The carbon-based air-water composite gel was applied to NaCl solutions of different concentrations to test the evaporation performance of the material in high-salinity seawater. The test results are shown in Fig. 9 The evaporation rate of the carbon-based air-water composite gel remains stable in NaCl solutions of different concentrations. This indicates that the carbon-based air-water composite gel can handle high-concentration salt water and has long-term stability.
[0048] Example 3
[0049] (1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0050] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0051] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0052] 0.1g tannic acid, 7.5g PVA, 10g ethanol, and 82.5g water were added to a beaker and heated and stirred until dissolved. Then, the mixture was added dropwise to the surface of CNFA (tannic acid / PVA solution: CNFA = 20g: 1g). After a few minutes, the solution was evenly diffused, frozen at -20°C for 8h, and then thawed for 8h, and the cycle was repeated 3 times to obtain a carbon-based air-water composite gel.
[0053] (2) Seawater desalination performance test:
[0054] A solar-simulated xenon lamp was used as the light source, and a 3g / 100mL sea salt solution was used to simulate seawater. A seawater desalination evaporation device was constructed using carbon-based air-water composite gel: EPE foam was used as the supporting material, and the carbon-based air-water composite gel was stuck in the hole in the center of the foam. The height of the carbon-based air-water composite gel exposed to the water surface was adjusted to 4 cm, and a beaker was used as a seawater container. The light intensity of the solar-simulated xenon lamp was adjusted to 1 kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. Figure 4 , and its evaporation rate is 4.26 kg m -2 h -1 . Continuous evaporation for 10 hours results are shown in Figure 5 , the evaporation rate can remain stable.
[0055] Example 4
[0056] (1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0057] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0058] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0059] 0.1g tannic acid, 2.5g PVA, 10g ethanol, and 87.5g water were added to a beaker and heated and stirred until dissolved. Then, the mixture was added dropwise to the surface of CNFA (tannic acid / PVA solution: CNFA = 20g: 1g). After a few minutes, the solution was evenly diffused, frozen at -20°C for 8h, and then thawed for 8h, and the cycle was repeated 3 times to obtain a carbon-based air-water composite gel.
[0060] (2) Seawater desalination performance test:
[0061] A solar-simulated xenon lamp was used as the light source, and a 3g / 100mL sea salt solution was used to simulate seawater. A seawater desalination evaporation device was constructed using carbon-based air-water composite gel: EPE foam was used as the supporting material, and the carbon-based air-water composite gel was stuck in the hole in the center of the foam. The height of the carbon-based air-water composite gel above the water surface was adjusted to 4cm, and a beaker was used as a seawater container. The light intensity of the solar-simulated xenon lamp was adjusted to 1kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. Figure 4 , and its evaporation rate is 3.9 kg m -2 h -1 . Continuous evaporation for 10 hours results are shown in Figure 5 , the evaporation rate can remain stable.
[0062] Comparative Example 1
[0063] 1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0064] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0065] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0066] A 5.56 wt.% PVA aqueous solution was added dropwise onto the CNFA surface (PVA solution: CNFA = 20 g: 1 g). After a few minutes, the solution was evenly diffused, frozen at -20°C for 8 h, and then thawed for 8 h, and the cycle was repeated 3 times to obtain a carbon-based air-water composite gel.
[0067] (2) Seawater desalination performance test:
[0068] A solar-simulated xenon lamp was used as the light source, and the simulated seawater was a 3g / 100mL sea salt solution. The carbon-based air-water composite gel was used to construct a seawater desalination evaporation device: the pearl cotton foam was used as the supporting material, and the carbon-based air-water composite gel was stuck in the hole in the center of the foam. The height of the carbon-based air-water composite gel exposed to the water surface was adjusted to 4cm, and a beaker was used as a seawater container. The light intensity of the solar-simulated xenon lamp was adjusted to 1kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. Figure 4 .from Figure 4 It can be seen that the evaporation rate is 3.49 kg m -2 h -1 Due to the lack of tannic acid, the evaporation rate is reduced. The results of continuous evaporation for 10 hours are shown in Figure 5 , the evaporation rate can remain stable.
[0069] Comparative Example 2
[0070] 1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0071] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0072] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0073] 0.1 g tannic acid, 5 g PVA, 10 g ethanol, and 85 g water were added to a beaker and heated and stirred until dissolved. CNFA was soaked in the above solution. Freeze at -20 °C for 8 h, then thawed for 8 h, and cycled for 3 times to obtain a carbon-based air-water composite gel.
[0074] The scanning electron microscopy image of the prepared carbon-based air-water composite gel is shown in Figure 3 As shown in Figure 2, the pores inside the aerogel are blocked by the hydrogel, leaving almost no gaps.
[0075] (2) Seawater desalination performance test:
[0076] A solar-simulated xenon lamp was used as the light source, and the simulated seawater was a 3g / 100mL sea salt solution. The carbon-based air-water composite gel was used to construct a seawater desalination evaporation device: the pearl cotton foam was used as the supporting material, and the carbon-based air-water composite gel was stuck in the hole in the center of the foam. The height of the carbon-based air-water composite gel exposed to the water surface was adjusted to 4cm, and a beaker was used as a seawater container. The light intensity of the solar-simulated xenon lamp was adjusted to 1kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. Figure 4 .from Figure 4 It can be seen that the evaporation rate is 2.98 kg m -2 h -1 . Continuous evaporation for 10 hours results are shown in Figure 5 As the illumination time increases, the evaporation rate gradually decreases. This is due to insufficient water supply. The photos of comparative example 2 before and after evaporation in 20wt.% concentrated brine for 10h are shown in Figure 7 After 10 hours of evaporation, the part exposed to the water surface shrinks significantly and cannot be used for a long time.
[0077] Comparative Example 3
[0078] 1) 7 g of PAN was added to 50 mL of DMF solvent and magnetically stirred at 60 °C for 10 h to obtain a uniform solution for electrospinning. The applied voltage and injection rate were set to 18 kV and 2 mL / h, respectively, and the distance between the needle and the collector was controlled at 12 cm. After 12 hours of electrospinning, a PAN nanofiber membrane was obtained.
[0079] 1 g of PAN nanofiber membrane was added to 200 mL of 0.5 wt.% SA aqueous solution and stirred at 32000 rpm in a high-speed disperser for 10 min. The obtained dispersion was poured into a cylindrical mold with a diameter of 3 cm and a height of 10 cm, frozen at -20°C for 12 h, and then freeze-dried for 48 h to obtain a composite aerogel NFA.
[0080] The obtained NFA was calcined at 500°C in a nitrogen atmosphere for 2 h, with a heating rate of 5°C / min and a nitrogen flow rate of 0.15 L / min, to obtain a composite carbon aerogel (CNFA) with a diameter of 1.5-1.6 cm and a height of 5-5.5 cm.
[0081] 0.1g tannic acid, 5g PVA, 10g ethanol, and 85g water were added to a beaker and heated and stirred until dissolved. Then, the mixture was added dropwise to the surface of CNFA (tannic acid / PVA solution: CNFA = 20g: 1g). After a few minutes, the solution was evenly diffused, frozen at -20°C for 8h, and then thawed for 8h, and the cycle was repeated 3 times to obtain a carbon-based air-water composite gel.
[0082] (2) Seawater desalination performance test:
[0083] A solar-simulated xenon lamp was used as the light source, and the simulated seawater was a 3g / 100mL sea salt solution. The carbon-based air-water composite gel was used to construct a seawater desalination evaporation device: the pearl cotton foam was used as the supporting material, and the carbon-based air-water composite gel was stuck in the hole in the center of the foam. The height of the carbon-based air-water composite gel exposed to the water surface was adjusted to 0 cm, and a beaker was used as a seawater container. The light intensity of the solar-simulated xenon lamp was adjusted to 1kW m -2 , place the container on a precision balance and record the change in the container mass during the evaporation process. Figure 4 .from Figure 4 It can be seen that due to the reduction of the lateral area, the evaporation rate is reduced to 2.01 kg m -2 h -1 .
[0084] The above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit and essence of this invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based gas-water composite gel for efficient interfacial evaporation, characterized in that: The method comprises the following steps: step 1, using N, N-dimethylformamide (DMF) solution of polyacrylonitrile (PAN) as spinning solution, wherein the concentration of PAN is 10-15wt.%, and obtaining PAN nanofiber membrane by electrostatic spinning; step 2, mixing the PAN nanofiber membrane with sodium alginate aqueous solution, wherein the mass ratio of PAN to sodium alginate (SA) is 1:(0.8-1.2), and stirring to obtain PAN / SA uniform dispersion; step 3, pouring the PAN / SA uniform dispersion into a mold, and freeze-drying to obtain a composite aerogel; step 4, calcining the composite aerogel for 1-3 h to obtain a composite carbon aerogel; step 5, dripping a tannic acid / PVA solution on the surface of the composite carbon aerogel, wherein the concentration of tannic acid in the solution is 0.1-0.5 wt.%, and the concentration of PVA is 2.5-7.5 wt.%, and the mass of the dripped solution is 15-25 times the mass of the aerogel, and then freezing and thawing for 1-5 times to obtain a carbon-based air-water composite gel.
2. The preparation method according to claim 1, characterized in that: In step 1, the weight average molecular weight of PAN is 149,000-151,000, and the concentration of PAN in the DMF solution of PAN is 13 wt.%.
3. The preparation method according to claim 1, characterized in that: In step 1, the electrospinning voltage was 18-21 kV, the liquid feeding rate was 1.5-3 mL / h, the distance between the needle and the receiver was 12 cm, and the spinning time was 12 h.
4. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the sodium alginate (SA) solution is 0.5wt.%~1wt.%, and the mass ratio of PAN to SA is 1:
1.
5. The preparation method according to claim 1, characterized in that: In step 2, the stirring speed is 30000-32000 rpm, and the stirring time is 10-15 min.
6. The preparation method according to claim 1, characterized in that: In step 4, the heating rate of the calcination is 5°C / min, and the nitrogen flow rate is 0.1-0.2 L / min.
7. The preparation method according to claim 1, characterized in that: In step 5, the concentration of tannic acid is 0.1 wt.%, the concentration of PVA is 5 wt.%, the solvent is a mixture of ethanol and water, and the volume ratio of ethanol to water is 1:
9.
8. The preparation method according to claim 1, characterized in that: In step 5, the freezing temperature is -20°C, the freezing time is 7.5-8.5 h, the thawing temperature is 10-25°C, and the thawing time is 8-10 h.
9. The carbon-based air-water composite gel prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the carbon-based air-water composite gel according to claim 9 in solar interfacial evaporation seawater desalination.
